2021
DOI: 10.1111/jpn.13577
|View full text |Cite
|
Sign up to set email alerts
|

Dry matter intake, digestibility, nitrogen utilization and fermentation characteristics of sheep fed Atriplex hay‐based diet supplemented with discarded dates as a replacement for barley grain

Abstract: Atriplex sp. is widely distributed in arid, semi-arid and Saharan regions of the world. It grows naturally as a fodder in these areas because of its great resistance to drought and high tolerance to salt (El Shaer, 2010;Shawket et al., 2010;Walker et al., 2014). The protein content in Atriplex sp. is more complex than traditional feed resources and it ranges between 100 and 250 g/kg DM. Atriplex sp. has high concentration of non-protein nitrogen compounds (NPN) such as free amino acids and nitrates that contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…It has been noted that at pH values below 6.0, cellulolytic (Takizawa et al., 2020 ) and fibrolytic activities decline (Chiba, 2014 ). Additionally, the findings of Khattab and Anele ( 2022 ), which the results of this experiment support, indicated that raising the pH of rumen fluid from 5.94 to 6.31 increased the nutrients digestibility. In general, the presence of NPN sources enhances microbial protein synthesis, increasing degradability.…”
Section: Discussionsupporting
confidence: 68%
“…It has been noted that at pH values below 6.0, cellulolytic (Takizawa et al., 2020 ) and fibrolytic activities decline (Chiba, 2014 ). Additionally, the findings of Khattab and Anele ( 2022 ), which the results of this experiment support, indicated that raising the pH of rumen fluid from 5.94 to 6.31 increased the nutrients digestibility. In general, the presence of NPN sources enhances microbial protein synthesis, increasing degradability.…”
Section: Discussionsupporting
confidence: 68%
“…Lower degradation of CN could be attributed to higher NDF, phenols, and tannins, which confirm that the chemical composition of fodder shrubs affected the rumen microbiota and the ruminal degradation [33,34]. On the other hand, higher degradation in the atriplex could be attributed to higher content of non-protein nitrogen compounds [38]. Previous studies found that the rumen disappearance of the diet's nutrients was declined by the inclusion of acacia, leucaena, and atriplex in the animal diet [3,39].…”
Section: Plos Onementioning
confidence: 59%
“…However, Abo-Donia et al (2019) reported that no significant increase in DMI was observed by dairy cows fed discarded dates. Also, no significant differences in DMI were found in sheep and lactating ewes fed discarded dates (Khattab, 2013;Khattab and Anele, 2022). Numerous studies have investigated the influence of discarded dates on nutrient digestion (Al-Yousef et al, 1994;Iqbal et al, 2019;Khattab et D al., 2013;Khattab and Anele, 2022;Shi et al, 2014;Taghinejad-Roudbaneh et al, 2015;Zade et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Also, no significant differences in DMI were found in sheep and lactating ewes fed discarded dates (Khattab, 2013;Khattab and Anele, 2022). Numerous studies have investigated the influence of discarded dates on nutrient digestion (Al-Yousef et al, 1994;Iqbal et al, 2019;Khattab et D al., 2013;Khattab and Anele, 2022;Shi et al, 2014;Taghinejad-Roudbaneh et al, 2015;Zade et al, 2014). Khattab and Anele (2022) reported that the digestibility of organic matter (OM), crude protein (CP), and neutral detergent fiber (NDF) were increased linearly (p<0.05) with increasing levels of dates, whereas the digestibility of dry matter (DM) tended to improve.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation